Satelleti Tracking and Sighting Data Analyses of Southeast Pacific Humpback Whales (Megaptera novaeangliae): Is the migratory Route Coastal or Oceanic? - Fernando, Félix (2014)
This paper presents an analysis of the migration movements of Southeast Pacific humpback whales (Megaptera novaeangliae) based on satellite and sighting data. We used information obtained from six humpback whales tagged off the coast of Ecuador between August and september 2013.